Development of Guided Inquiry-Based Flipped Classroom Learning (FGIL) on Petroleum Materials with Moodle for SMA/MA - Firmansyah Khairul Kamal; Basultan Hidayat; M. Riski (INTERNATIONAL JOURNAL OF HIGH INFORMATION, COMPUTERIZATION, ENGINEERING AND APPLIED SCIENCE (JHICE), 2022)
The advent of the Covid-19 pandemic has influenced many aspects of life, especially the world of education. One of them is the SMA / MA level, which allows you to activate your learning system online. Therefore, information is needed in the form of a learning system called e-learning that can support learning activities. This study aims to develop a flipped classroom (FGIL) based on guided learning of petroleum materials using Moodle for SMA / MA. This study is categorized as R & D with 4D development models. The e-learning products in this study were validated by 4 chemistry teachers, and validity and practicality test analysis were performed by 3 teachers and 10 students in SMAN 6 Padang using the VAiken formula. It was analyzed. Aiken's V-scores, obtained from the validity of the construct and the validity of the content, are 0.88 and 0.89, which is a high category. The results of practical relationships between students and teachers are in the high categories of 84.38 and 87.29, respectively. Based on the results of the data analysis, we can conclude that the content of e-learning is valid and practical to use in the learning process.